Method for detecting content of zirconium element in magnesite

Through steps such as acid solution dissolution and perchloric acid evaporation, combined with nitric acid dissolution and spectrophotometer determination, the problem of detecting the content of zirconium in magnesite in the prior art is solved, and a fast and accurate detection effect is achieved.

CN119757247APending Publication Date: 2025-04-04BENGANG STEEL PLATES CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411656614.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately detect the content of zirconium in magnesite, which makes it difficult to accurately control the chemical composition of molten iron and steel in the metallurgical industry.

Method used

After the sample was dissolved in the acid solution, hydrofluoric acid and perchloric acid were added in turn, and after heating and evaporation, the zirconium standard solution was prepared with nitric acid, and the absorbance was measured by spectrophotometer. The content of zirconium in magnesite was calculated based on the standard curve.

Benefits of technology

It realizes rapid and accurate detection of the content of zirconium in magnesite, reduces the difficulty of sample preparation and detection operations, and overcomes the shortcomings of traditional methods such as complex operation, high cost and low efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005142249550000021
    Figure BDA0005142249550000021
  • Figure BDA0005142249550000061
    Figure BDA0005142249550000061
  • Figure BDA0005142249550000062
    Figure BDA0005142249550000062
Patent Text Reader

Abstract

The invention discloses a method for detecting the content of a zirconium element in magnesite, which comprises the following steps: dissolving a sample with an acid solution, sequentially adding hydrofluoric acid and perchloric acid, heating to evaporate and smoke until nearly dry, cooling, dissolving salts with nitric acid, and uniformly mixing with water at a constant volume to obtain a to-be-detected sample solution; preparing a blank solution according to the same method; preparing a zirconium standard solution; preparing a developing solution and a reference solution; measuring absorbance of the developing solution and the reference solution of the zirconium standard solution by adopting a spectrophotometer to obtain a standard curve, measuring absorbance of the developing solution and the reference solution of the to-be-measured sample solution and the developing solution and the reference solution of the blank solution under the same condition, and obtaining the content of the zirconium element in the to-be-measured sample solution according to the standard curve. And calculating to obtain the content of the zirconium element in the magnesite. The detection method disclosed by the invention is accurate and reliable, is simple and convenient to operate, not only can improve the detection efficiency and the detection precision of the zirconium element content, but also reduces the operation difficulty of sample preparation and sample detection, and has important popularization value and practical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials and metallurgy, and more specifically, to a method for detecting the content of zirconium in magnesite. Background Art

[0002] Refractory materials are currently the most important lining materials for various high-temperature kilns and furnaces, and they play an extremely important role in the metallurgical industry. Magnesite, as an important calcium and magnesium resource, is one of the indispensable raw materials for refractory materials.

[0003] Zirconium is a very important chemical component in steel. It is an element that reduces the y phase area. As an alloying element in steel, it has a significant effect on improving the hardenability of steel when dissolved in austenite. Zirconium has a strong affinity with oxygen, nitrogen and sulfur. It is a powerful deoxidizer that can purify steel. It combines with sulfur to form zirconium sulfide ZrS, which can effectively prevent the occurrence of hot brittleness of steel. For free-cutting steel, it can significantly improve its cutting performance and high-temperature forgeability. Improve the density of weld metal and eliminate the porous and loose phenomena of welds. Improve the low-temperature toughness of steel. Zirconium is an element that strengthens the formation of carbon and nitrogen compounds. It forms stable compounds ZrC and ZrN with carbon and nitrogen respectively. Its beneficial effects are: fixing carbon, refining grains, improving the blue brittleness of steel, preventing the depletion of chromium at grain boundaries, and reducing or eliminating the intergranular corrosion tendency of stainless steel.

[0004] During the iron-making and steel-making stages, molten iron and molten steel will come into direct contact with refractory materials, so the chemical component zirconium in refractory materials will inevitably enter the molten iron and molten steel. Therefore, it is urgent to develop a method for detecting the zirconium content in magnesite with simple processing steps, low cost, rapid detection and accurate detection, so as to provide a scientific basis for accurately controlling and analyzing the sources of chemical components in molten iron and molten steel. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a method for detecting the zirconium content in magnesite, which significantly improves the accuracy and precision of the measurement results while ensuring rapid detection.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A method for detecting the zirconium content in magnesite comprises the following steps:

[0008] (1) Dissolve the sample in acid solution, then add hydrofluoric acid and perchloric acid in sequence, heat and evaporate until fuming, cool and dissolve the salt in nitric acid, dilute to volume with water, mix well, and obtain the sample solution to be tested; prepare a blank solution in the same way;

[0009] (2) preparing a zirconium standard solution: after selecting a zirconium oxychloride standard reagent, using nitric acid to prepare a zirconium standard solution with a gradient concentration of 1 μg / mL to 10 μg / mL;

[0010] (3) Prepare the color developing solution and reference solution:

[0011] Take two equal amounts of the sample solution to be tested; add urea and nitric acid to one of the sample solutions to be tested in sequence, mix them, then add arsenazo III, and dilute with water to obtain a color developing solution; add ammonium fluoride to the other sample solution to obtain a reference solution;

[0012] At the same time, prepare the color developing solution and reference solution of the blank solution and the color developing solution and reference solution of the zirconium standard solution respectively in the same manner;

[0013] (4) Using a spectrophotometer to measure the absorbance of the colorimetric solution and the reference solution of the zirconium standard solution to obtain a standard curve, and under the same conditions, measuring the absorbance of the colorimetric solution and the reference solution of the test sample solution and the colorimetric solution and the reference solution of the blank solution, according to the standard curve, the content of zirconium in the test sample solution is obtained, and the content of zirconium in magnesite is calculated according to the following formula:

[0014]

[0015] Where: w Zr —mass fraction of zirconium, %; C—content of zirconium in the test sample solution, μg / mL; C0—detection value of blank solution, μg / mL; V—total volume of the test sample solution, mL; m—mass of the sample, μg.

[0016] Implementing the embodiments of the present invention will have the following beneficial effects:

[0017] The embodiment of the present invention provides a method for detecting the content of zirconium in magnesite. First, the sample is dissolved in acid solution, and hydrofluoric acid is used to destroy acid-insoluble zirconium, perchloric acid is smoked to drive fluorine, hydrogen peroxide is used to reduce chromium, and titanium is complexed. In a nitric acid medium, in the presence of urea, it is complexed with azoarsine III to form a red complex, and photometric determination is performed. The detection method of the present invention is accurate and reliable, and the operation is simple. It can not only improve the detection efficiency and detection accuracy of the zirconium content, but also reduce the difficulty of sample preparation and sample detection operation, overcome the shortcomings of traditional inspection methods such as complex operation, high cost and low efficiency, and narrow measurement range, and is suitable for the determination of zirconium content with a mass fraction of 0.0003% to 1.0% in magnesite, and has important promotion value and practical value. DETAILED DESCRIPTION

[0018] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0019] The invention discloses a method for detecting the content of zirconium in magnesite, comprising the following steps:

[0020] (1) Dissolve the sample in acid solution, then add hydrofluoric acid and perchloric acid in sequence, heat and evaporate until fuming, cool and dissolve the salts in nitric acid, make up to volume with water, mix well, and obtain the sample solution to be tested; prepare the blank solution in the same way.

[0021] In a specific embodiment, step (1) specifically includes the following steps: placing 0.10g to 2.0g of a sample in a polytetrafluoroethylene beaker, adding 10mL to 50mL of an acid solution to dissolve the sample, then adding 4mL to 20mL of hydrofluoric acid and 10mL to 30mL of perchloric acid in sequence, heating and evaporating at 220°C to 400°C until white perchloric acid smoke is emitted, washing the container wall with water to remove all hydrofluoric acid, continuing to heat and evaporate until 1ml to 4ml remains, cooling, dissolving the salts with 5mL to 25ml of nitric acid (4+1), diluting the volume to 50mL or 100mL with water, and mixing; a blank solution is prepared in the same manner.

[0022] In a specific embodiment, the acid solution includes nitric acid (1+1) and / or hydrochloric acid.

[0023] (2) Preparation of zirconium standard solution: After selecting zirconium oxychloride standard reagent, use nitric acid to prepare a zirconium standard solution with a gradient concentration of 1 μg / mL to 10 μg / mL.

[0024] In a specific embodiment, step (2) specifically includes the following steps:

[0025] (2.1) Bake zirconium oxychloride standard reagent at 100°C for 1 hour and cool to room temperature. Weigh 0.1766 g and add 100 ml of nitric acid (1+3) to dissolve. After cooling to room temperature, dilute to 1000 ml with nitric acid (1+3) and mix well to obtain a zirconium stock solution with a concentration of 50 μg / mL.

[0026] (2.2) Take 2 mL, 4 mL, 10 mL, and 20 mL of the zirconium stock solution in turn, and add 100 mL of nitric acid (1+3) respectively. After constant volume, prepare zirconium standard solutions with zirconium concentrations of 1 μg / mL, 2 μg / mL, 5 μg / mL, and 10 μg / mL respectively.

[0027] (3) Preparation of color developing solution and reference solution: Take two equal amounts of the sample solution to be tested; add urea and nitric acid in sequence to one of the sample solution to be tested, mix them, then add arsenazo III, and dilute to volume with water to obtain a color developing solution; add ammonium fluoride to the other sample solution to dilute to obtain a reference solution; and simultaneously prepare the color developing solution and reference solution of the blank solution and the color developing solution and reference solution of the zirconium standard solution in the same manner.

[0028] In a specific embodiment, in step (3), the preparation process of the color developing solution and the reference solution is as follows: take two equal amounts of the test sample solution; add 1 ml to 4 ml of urea and 15 ml to 35 ml of nitric acid to one of the 5.00 ml to 50.00 ml test sample solutions in sequence, mix for 10 min to 30 min, then add 1 ml to 5 ml of arsenazo III, and dilute with water to obtain a color developing solution; add 3 drops to 15 drops of ammonium fluoride to the other 5.00 ml to 50.00 ml test sample solution, and dilute to obtain a reference solution.

[0029] In a specific embodiment, the concentration of urea is 100 g / L to 300 g / L; the concentration of arsenazo III is 1 g / L to 8 g / L; and the concentration of ammonium fluoride is 100 g / L to 500 g / L.

[0030] (4) Using a spectrophotometer, the absorbance of the colorimetric solution and the reference solution of the zirconium standard solution is measured to obtain a standard curve. Under the same conditions, the absorbance of the colorimetric solution and the reference solution of the test sample solution and the colorimetric solution and the reference solution of the blank solution is measured. According to the standard curve, the content of zirconium in the test sample solution is obtained, and the content of zirconium in magnesite is calculated according to the following formula:

[0031] In a specific embodiment, step (4) specifically includes the following steps: placing the sample color developing solution and the sample reference solution in an absorption dish of 1 cm, 2 cm or 3 cm, taking the reference solution as a reference, measuring the absorbance at 560 nm to 810 nm using a spectrophotometer, obtaining the zirconium content in the test sample solution and the blank solution detection value, and calculating the zirconium content in magnesite.

[0032] In a specific embodiment, the mass content of zirconium in the sample is 0.0003% to 1.0%.

[0033] The following are specific embodiments

[0034] Example 1

[0035] 1. Reagents: Unless otherwise specified, only analytical grade reagents and distilled water or water of equivalent purity should be used during analysis.

[0036] 1.1 Nitric acid, 1.42 g / mL, 1+1, 4+1, 1+3;

[0037] 1.2 Hydrofluoric acid, 1.15 g / mL;

[0038] 1.3 hydrochloric acid, 1.19 g / mL, 1+1;

[0039] 1.4 Phosphoric acid, 1+2;

[0040] 1.5 Hydrogen peroxide, 0.90 g / mL;

[0041] 1.6 Perchloric acid, 1.67 g / mL;

[0042] 1.7 Urea, 150g / L;

[0043] 1.8 Arsenazo III, 2g / L, used after filtration;

[0044] 1.9 Ammonium fluoride, 400g / L.

[0045] 2. Experimental steps

[0046] (1) Weigh about 0.1000 g of the sample (accurate to 0.0001 g) and place it in a 125 ml polytetrafluoroethylene beaker. Add 20 ml of nitric acid (1+1) to dissolve the sample. Then add 5 ml of hydrofluoric acid and 10 ml of perchloric acid in sequence. Heat and evaporate at 220°C to 400°C until white perchloric acid smoke is emitted. Rinse the container wall with water to remove all the hydrofluoric acid. Continue heating and evaporating until 3 ml to 4 ml remain. Cool, dissolve the salts with 25 ml of nitric acid (4+1), make up to 100 ml with water, and mix well. Prepare a blank solution in the same way.

[0047] (2) Preparation of zirconium standard solution: Dry zirconium oxychloride standard reagent at 100°C for 1 hour and cool to room temperature, weigh 0.1766g and place in a 250mL beaker, add 100ml of nitric acid (1+3) to dissolve, cool to room temperature, transfer to a 1000mL volumetric flask, dilute to scale with nitric acid (1+3), mix well, and obtain a zirconium stock solution with a concentration of 50μg / mL. Use nitric acid (1+3) to dilute and prepare zirconium standard solutions with zirconium concentrations of 1μg / mL, 2μg / mL, 5μg / mL, and 10μg / mL, respectively.

[0048] Prepare the color developing solution and reference solution: take two 10.00mL portions of the sample solution to be tested and place them in 50mL volumetric flasks; add 2mL of urea and 25mL of nitric acid to one portion of the sample solution to be tested, mix for 10 minutes, then add 2mL of arsenazo III, and dilute with water to obtain the color developing solution; add 5 drops of ammonium fluoride to the other portion of the sample solution to be tested, and dilute to obtain the reference solution. At the same time, prepare the color developing solution and reference solution of the blank solution and the color developing solution and reference solution of the zirconium standard solution in the same way.

[0049] (5) The absorbance of the colorimetric solution and the reference solution of the zirconium standard solution was measured by a spectrophotometer. The standard curve was drawn with the mass of zirconium as the horizontal axis and the absorbance as the vertical axis. The sample colorimetric solution and the sample reference solution were placed in a 3 cm absorption dish. The reference solution was used as a reference. The absorbance was measured at 660 nm by a spectrophotometer to obtain the zirconium element content in the test sample solution and the blank solution detection value. The zirconium content in the magnesite production sample No. HB2307115 was calculated according to the following formula, as shown in Table 1.

[0050]

[0051] Where: w Zr —mass fraction of zirconium, %; C—content of zirconium in the test sample solution, μg / mL; C0—detection value of blank solution, μg / mL; V—total volume of the test sample solution, mL; m—mass of the sample, μg.

[0052] Example 2

[0053] The difference between this embodiment and embodiment 1 is that about 0.0200 g of the HB2405088 sample (accurate to 0.0001 g) is weighed, and the zirconium content test result of the magnesite production sample No. HB2405088 is obtained according to the calculation method of embodiment 1. As shown in Table 1.

[0054] Example 3

[0055] The difference between this embodiment and embodiment 1 is that about 2.000 g of HB2406013 sample (accurate to 0.0001 g) is weighed, and the test result of the zirconium content in the magnesite production sample No. HB2406013 is obtained according to the calculation method of embodiment 1, as shown in Table 1.

[0056] Table 1 Test results of Examples 1-3 According to the results in Table 1, the detection methods of Examples 1-3 of the present invention are accurate and reliable, which can not only improve the detection efficiency and detection accuracy of the zirconium content, but also reduce the difficulty of sample preparation and sample detection operations, and overcome the shortcomings of traditional inspection methods such as complex operation, high cost, low efficiency, and narrow measurement range.

[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for detecting the content of zirconium in magnesite, characterized in that: The following steps are involved: (1) Dissolve the sample in acid solution, then add hydrofluoric acid and perchloric acid in sequence, heat and evaporate until fuming, cool and dissolve the salt in nitric acid, dilute to volume with water, mix well, and obtain the sample solution to be tested; prepare a blank solution in the same way; (2) preparing a zirconium standard solution: after selecting a zirconium oxychloride standard reagent, using nitric acid to prepare a zirconium standard solution with a gradient concentration of 1 μg / mL to 10 μg / mL; (3) Prepare the color developing solution and reference solution: Take two equal amounts of the sample solution to be tested; add urea and nitric acid to one of the sample solutions to be tested in sequence, mix them, then add arsenazo III, and dilute to volume with water to obtain a color developing solution; Add ammonium fluoride to another sample solution to make up the volume to obtain a reference solution; At the same time, prepare the color developing solution and reference solution of the blank solution and the color developing solution and reference solution of the zirconium standard solution respectively in the same manner; (4) Using a spectrophotometer to measure the absorbance of the colorimetric solution and the reference solution of the zirconium standard solution to obtain a standard curve, and under the same conditions, measuring the absorbance of the colorimetric solution and the reference solution of the test sample solution and the colorimetric solution and the reference solution of the blank solution, according to the standard curve, the content of zirconium in the test sample solution is obtained, and the content of zirconium in magnesite is calculated according to the following formula: Where: w Zr —mass fraction of zirconium, %; C—content of zirconium in the test sample solution, μg / mL; C0—detection value of blank solution, μg / mL; V—total volume of the test sample solution, mL; m—mass of the sample, μg.

2. The method for detecting the zirconium content in magnesite according to claim 1, characterized in that: Step (1) Specific The following steps are involved: Place the sample in a polytetrafluoroethylene beaker, add acid solution to dissolve the sample, then add hydrofluoric acid with a mass concentration of 10% to 30% and perchloric acid with a mass concentration of 30% to 50% in sequence, and heat and evaporate at 220°C to 400°C until white perchloric acid smoke is emitted, wherein the mass volume ratio of the sample, acid solution, hydrofluoric acid, and perchloric acid is 0.10g to 2.0g: 10mL to 50mL: 4mL to 20mL: 10mL to 30ml, and rinse the container wall with water to remove all hydrofluoric acid, continue heating and evaporating until 1ml to 4ml remains, cool, use 5mL to 25ml of nitric acid (4+1) to dissolve the salts, dilute to 50mL or 100mL with water, and mix well; prepare a blank solution in the same way.

3. The method for detecting the zirconium content in magnesite according to claim 1, characterized in that: The acid solution includes nitric acid (1+1) and / or hydrochloric acid.

4. The method for detecting the zirconium content in magnesite according to claim 1, characterized in that: Step (2) specifically includes the following steps: The zirconium oxychloride standard reagent was first dried at 100°C for 1 hour and cooled to room temperature, 0.1766 g was weighed and added to 100 ml of nitric acid (1+3) to dissolve, cooled to room temperature, diluted to 1000 ml with nitric acid (1+3), and mixed to obtain a zirconium stock solution with a concentration of 50 μg / mL; After taking 2 mL, 4 mL, 10 mL, and 20 mL of the zirconium stock solution in turn, 100 mL of nitric acid (1+3) was added respectively, and after constant volume, zirconium standard solutions with zirconium concentrations of 1 μg / mL, 2 μg / mL, 5 μg / mL, and 10 μg / mL were prepared respectively.

5. The method for detecting the zirconium content in magnesite according to claim 1, characterized in that: In step (3), the preparation process of the color developing solution and the reference solution is as follows: Take two equal amounts of the test sample solution; To one portion of the test sample solution (5.00 mL to 50.00 mL), add 1 ml to 4 ml of urea and 15 ml to 35 ml of nitric acid, mix for 10 min to 30 min, then add 1 ml to 5 ml of arsenazo III, and dilute to volume with water to obtain a color developing solution; To another 5.00 mL to 50.00 mL of the sample solution to be tested, add 3 to 15 drops of ammonium fluoride and dilute to obtain a reference solution.

6. The method for detecting the zirconium content in magnesite according to claim 5, characterized in that: The concentration of the urea is 100 g / L to 300 g / L; the concentration of the arsenazo III is 1 g / L to 8 g / L; and the concentration of the ammonium fluoride is 100 g / L to 500 g / L.

7. The method for detecting the zirconium content in magnesite according to claim 1, characterized in that: Step (4) specifically includes the following steps: The sample color developing solution and the sample reference solution are placed in an absorption dish of 1 cm, 2 cm or 3 cm, and the reference solution is used as a reference. The absorbance is measured at 560 nm to 810 nm using a spectrophotometer to obtain the zirconium content in the test sample solution and the blank solution detection value, and the zirconium content in magnesite is calculated.

8. The method for detecting the zirconium content in magnesite according to claim 1, characterized in that: The mass content of zirconium in the sample is 0.0003% to 1.0%.

Citation Information

Patent Citations

  • Method for measuring zirconium in steel

    CN101408515A

  • Analysis method of zirconium content in copper alloy

    CN105403566A

  • Method for measuring zirconium content in magnesium alloy

    CN117607129A

  • Zirconium concentration analyzing method of ferro-silicon alloy by an inductively coupled plasma spectrometer for accurately and quickly analyzing density of zirconium among a sample

    KR1019990051986A